ANALISIS PENDAPATAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI PADI SAWAH DI KABUPATEN DELI SERDANG - Sarah Gracia; Elvin Desi Martauli (JEMBATAN, 2021)
The purpose of this study was to analyze income and the factors that influence the production of lowland rice farming in Deli Serdang Regency. The number of respondents of rice farmers in as many as 120 people. While the method used is the analysis of the Cobb-Douglas production function which is then converted into an inferential Principal Component Analysis (PCA) analysis, technical efficiency analysis with the stochastic frontier. The results showed that the factors of land area (X1), number of workers (X2), use of fertilizers (X3), pesticides (X4), and seeds (X5) had a significant effect on the production of lowland rice farming in Deli Serdang Regency. The results of the t test show that partially the factors that affect the production of land area, seeds, fertilizers, and labor have a significant effect on the productivity of lowland rice farming in Deli Serdang Regency. In the analysis of rice farming income in Meintang Market and Lubuk Pakam, Deli Serdang Regency, the total variable costs were Rp. 6,196.756, total fixed costs were Rp. 289.485. So that the level of income obtained by respondent farmers is Rp. 13,200,199.